2022
DOI: 10.1364/ao.452140
|View full text |Cite|
|
Sign up to set email alerts
|

High anti-interference dual-parameter sensor using EIT-like effect photonic crystal cavity coupled system

Abstract: We propose a sensor with high anti-interference ability using a photonic crystal cavity coupled system for simultaneous sensing of the refractive index (RI) and temperature (T) based on an electromagnetically induced transparency-like effect. A transparent window is achieved in the transmission spectrum through destructive interference between the air mode resonance and dielectric mode resonance in two one-dimensional photonic crystal structures. The T-sensitive material (SU-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The surface plasmon resonance driven photonic crystal fiber based biosensing structures are suggested by research groups of Qingli et al and Zhiwen et al [36,37]. Tongyu et al suggested the PC cavity coupled photonic sensor for simultaneously sensing refractive index and temperature by using an electromagnetically induced transparency effect [38]. Recently, Zina et al suggested how 1D PC consisting of cold magnetic plasma and quartz materials according to the Copper mean sequence can be used for the detection of the magnetic field direction by studying the external magnetic field dependent movement of ultra large PBG of the structure [39].…”
Section: Introductionmentioning
confidence: 99%
“…The surface plasmon resonance driven photonic crystal fiber based biosensing structures are suggested by research groups of Qingli et al and Zhiwen et al [36,37]. Tongyu et al suggested the PC cavity coupled photonic sensor for simultaneously sensing refractive index and temperature by using an electromagnetically induced transparency effect [38]. Recently, Zina et al suggested how 1D PC consisting of cold magnetic plasma and quartz materials according to the Copper mean sequence can be used for the detection of the magnetic field direction by studying the external magnetic field dependent movement of ultra large PBG of the structure [39].…”
Section: Introductionmentioning
confidence: 99%